Learning Outcomes in Science Subjects Through the Inkuri Learning Model in Elementary Schools - Aningsih, Aningsih; Dermawan, Deden Dicky; Habibah, Habibah (AS-SABIQUN, 2023)
This research is motivated by the low learning outcomes of elementary school students in science subjects in various regions of Indonesia, this is indicated by the large number of students who have not reached the specified KKM score. This problem is caused by the teacher not building a pleasant learning atmosphere and most students are less active, less motivated in learning and not given extensive opportunities to ask questions and express opinions. In such conditions the inquiry learning model can be a solution, because the inquiry learning model can involve students actively in the learning process. This study aims to examine the application of the inquiry learning model to science learning outcomes in elementary schools. The method used in this study is a Systematic Literature Review (SLR) by analyzing research results that have been published nationally related to the use of inquiry models on science learning outcomes in elementary schools. The sample for the analysis is 20 journal articles that have been published in the 2017-2022 range, from the twenty journals the researcher then analyzes from various aspects, namely: 1) based on the research method used, 2) journal area, 3) application of the inquiry learning model to science material in low and high grade elementary schools, 4) learning materials, 5) steps of inquiry learning model, 6) based on aspects of learning outcomes indicators in journal articles. Based on the results of the analysis of the inquiry learning model it is proven to be able to improve and have a positive effect on student learning outcomes in science subjects. In each journal article that has been analyzed there are differences in the results of the inquiry learning model but overall this study shows the conclusion that the inquiry learning model can improve learning outcomes and has a large influence on science learning outcomes in elementary schools